2012
DOI: 10.4071/hitec-thp12
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Carbide High Temperature Operational Amplifier

Abstract: Development of silicon carbide operational amplifier offers an attractive alternative building block for the replacement of silicon and silicon-on-insulator analog circuits in harsh environment applications. NMOS-based enhancement mode silicon carbide device technology was utilized to demonstrate feasibility of operational amplifiers for use in harsh environment applications. This study reports on the results of characterization of operational amplifiers at room temperature and high temperatures up to 350°C. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The measured low offset and high linearity of this amplifier demonstrates that the SiC BJT technology is suitable for front-end sensor circuits for high-temperature applications. [4] 300 76 3000 0.6@50ºC;25@300ºC 6H-SiC NMOS [7] 300 53 269 -4H-SiC NMOS [8] 350 60 ~200 35@27ºC;150@350ºC 4H-SiC NMOS [9] 300 42 ~100 -4H-SiC NMOS [10] 500 55 ~1000 -6H-SiC JFET [11] 576 69 1400 *…”
Section: Discussionmentioning
confidence: 99%
“…The measured low offset and high linearity of this amplifier demonstrates that the SiC BJT technology is suitable for front-end sensor circuits for high-temperature applications. [4] 300 76 3000 0.6@50ºC;25@300ºC 6H-SiC NMOS [7] 300 53 269 -4H-SiC NMOS [8] 350 60 ~200 35@27ºC;150@350ºC 4H-SiC NMOS [9] 300 42 ~100 -4H-SiC NMOS [10] 500 55 ~1000 -6H-SiC JFET [11] 576 69 1400 *…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that for MOSFET based integrated circuits, all-FET design is advantageous compared to the enhancement mode MOSFET and n-channel resistors because for the all-FET design, the device parameters were found to drift in the same direction with temperature. This led towards a robust design capable of stable operation over a wide temperature range [7]. Therefore, in this letter, a ring oscillator circuit and op-amp were designed using the all enhancement mode NMOS approach.…”
Section: Device Design and Fabricationmentioning
confidence: 99%
“…Finally, a titanium, tungsten and gold metal stack was deposited as bond pad contacts and metal interconnects. The design and fabrication of the SiC integrated circuits followed techniques outlined in [7]. It has been previously reported that for MOSFET based integrated circuits, all-FET design is advantageous compared to the enhancement mode MOSFET and n-channel resistors because for the all-FET design, the device parameters were found to drift in the same direction with temperature.…”
Section: Device Design and Fabricationmentioning
confidence: 99%